Nobiletin restores the intestinal barrier of HFD-induced obese mice by promoting MHC-II expression and lipid metabolism - Ni Yang; Yue-Shan Pang; Yali Zheng; Yan-Ju Gong; Wei-Jun Ding (Molecular Medicine)
Abstract The incidence of obesity is increasing annually worldwide. A high-fat diet (HFD) causes intestinal barrier damage, but effective interventions are currently unavailable. Our previous work demonstrated the therapeutic effect of nobiletin on obese mice; thus, we hypothesized that nobiletin could reverse HFD-induced damage to the intestinal barrier. Male C57BL/6 J mice were orally administered nobiletin for 14 d. After identification, the obese mice were equally divided into three groups: the HFD group, the low-dose (NOL, 100 mg/kg/d) group and the high-dose nobiletin (NOH, 200 mg/kg/d) group. A normal control group (CON) was also included. Hematoxylin and eosin (HE) staining and immunofluorescence were used to observe the intestinal barrier. RT-qPCR was used to determine the transcriptomic levels of genes involved in intestinal barrier integrity and lipid metabolism. The results revealed that intestinal tight proteins, including ZO-1 and Occludin, were significantly reduced in HFD-fed mice but markedly restored after nobiletin intervention, particularly in NOH mice. Improvements in the intestinal barrier and lipid metabolism associated with major histocompatibility complex class II (MHC-II) and relevant elements were revealed after nobiletin intervention. Enrichment analysis revealed that MHC-II plays an important role in the restoration of the intestinal barrier. Taken together, nobiletin restored intestinal barrier integrity and lipid metabolism by regulating MHC-II expression.